(Παλαιό) Χαρμάνκιοϊ Ιστορία, δημογραφία (τέλη 18ου αι. – αρχές δεκαετίας 1930) - Χατζηκυριακίδης Κυριάκος Στ. (Μακεδονικά, 2011)
The present article presents the history and demography of the (Old)Harmankioi, from the end of the 18th century to the 30s. It is a settlementin the western area of Thessaloniki, mentioned in the sources ever since thebeginning of the 17th century. The big Ottoman estate and the homonymoussmall settlement, owing their name to the grain areas, were inhabited byfarmers of the Thessaloniki fields and then the Vlachs of Paikos.In the beginning of the 20th century the Harmankioi was the center ofevolution since it was one of the main places that welcomed the eradicatedGreeks of the East. Thousands of refugees passed through the area, to finally spread all over northern Greece. Along with the indigenous and the Vlachsof the first settlement having St. Athanasios church as a core, they wererefugees from Smyrna and especially Koukloutza – a renowned suburb ofSmyrna – who settled there. The article couldn’t lack a short reference to therelation between the indigenous and the refugees as well as their political behaviour. The financial transactions, the elementary school and the commoneveryday problems of the poor agro-cattling settlement were the main factorsof the population homogenization. The (Old) Harmankioi was renamed toNew Koukloutzas in the 30s, according the favourite refugees’ tactic to«transfer» the names of their homelands to their new places of residence inGreece. In June 1955 the settlement was named Evosmon, and finally after1960 and up until today Evosmos.